The Influence of Dust Soiling on the Performance of Photovoltaic Modules in the Semi-Arid Areas of South Africa - Du Plessis, Armand (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.